Encrypted Client Hello (ECH) in Censorship Circumvention - Niere, Niklas; Lange, Felix; Heitmann, Nico; Somorovsky, Juraj
Censors have long censored Transport Layer Security (TLS) traffic by inspecting the domain name in the unencrypted Server Name Indication (SNI) extension. By encrypting the SNI extension, the Encrypted ClientHello (ECH) prevents censors from blocking TLS traffic to certain domains. Despite this promising outlook, ECH’s current capability to contest TLS censorship is unclear; for instance, Russia has started censoring ECH connections successfully. This paper clarifies ECH’s current role for TLS censorship. To this end, we evaluate servers’ support for ECH and its analysis and subsequent blocking by censors. We determine Cloudflare as the only major provider supporting ECH. Additionally, we affirm previously known ECH censorship in Russia and uncover indirect censorship of ECH through encrypted DNS censorship in China and Iran. Our findings suggest that ECH’s contribution to censorship circumvention is currently limited: we consider ECH’s dependence on encrypted DNS especially challenging for ECH’s capability to circumvent censorship. We stress the importance of censorship-resistant ECH to solve the long-known problem of SNI-based TLS censorship.
Keywords: censorship; circumvention; ECH; TLS

Differences of producing head fakes with and without a social partner - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 57th Annual Conference of the German Association of Sport Psychology)

Balkonkraftwerke kompakt für Dummies - Krauter, Stefan; Ofenheusle, Christian; Haselhuhn, Ralf

Schulisches Wohlbefinden von Schüler*innen der Sekundarstufe I in inklusiven Lerngruppen – Analysen zum Entwicklungsverlauf an der Laborschule Bielefeld - Marker, Rabea; Kullmann, Harry; Zentarra, Dominik; Geist, Sabine; Lütje-Klose, Birgit (Zeitschrift für Pädagogik)
Das schulische Wohlbefinden von Schüler*innen kann durch die Gestaltung der Lernumgebung positiv beeinflusst werden. Daher gilt es, entsprechend wirkungsvolle Unterrichtsmerkmale zu identifizieren. Am Beispiel der Laborschule Bielefeld, einer Versuchsschule des Landes Nordrhein-Westfalen wurde der Einfluss der Merkmale Wertschätzung durch die Lehrkräfte, individuelle Unterstützung, stärkenorientierte Diagnostik sowie unterrichtsbezogene Partizipation auf das schulische Wohlbefinden von Schüler*innen aus inklusiven Lerngruppen der Jahrgangsstufen 6 bis 8 untersucht. Die Mehrebenenanalysen zeigen, dass die untersuchten Unterrichtsmerkmale das schulische Wohlbefinden positiv beeinflussen. Der Effekt einzelner Unterrichtsmerkmale verändert sich teilweise über die Jahrgangsstufen.
Keywords: Selbsteinschätzung; Wertschätzung; Wohlbefinden; Pädagogische Diagnostik; Schule; Schuljahr 6; Schuljahr 7; Schuljahr 8; Sekundarstufe I; Laborschule; Lehrer; Schüler; Individualisierung; Lerngruppe; Unterrichtsgestaltung; Mitbestimmung; Empirische Untersuchung; Fragebogen; Längsschnittuntersuchung; Mehrebenenanalyse; Inklusion; Einflussfaktor; Unterstützung; Bielefeld; Deutschland

Dimensiones transnacionales y multilingües de la educación intercultural: Resultados de una encuesta a futuros docentes en Badajoz (España) y Posadas (Argentina) - Pöllmann, Andreas (Revista La Rivada)
Basado en una encuesta en línea efectuada a futuros docentes en Badajoz (España) y Posadas (Argentina), el presente artículo explora competencias multilingües y formas de educación intercultural más allá de las fronteras nacionales. Los datos cuantitativos obtenidos demuestran que, en ambas ciudades, la gran mayoría de los futuros docentes considera que los conocimientos sobre sistemas educativos de otros países, la inclusión de recursos didácticos bi- o multilingües y la inclusión de temas interculturales son importantes o muy importantes. Además, muchos de los futuros profesionales de la educación cuentan con capital intercultural que se podría aplicar en diferentes contextos nacionales y transnacionales de enseñanza y aprendizaje interculturales. Sin embargo, para poder aprovechar plenamente su potencial, es crucial crear contextos educativos más equitativos e incluyentes que traten de superar los desequilibrios sistemáticos en las oportunidades de realización del capital intercultural.
Keywords: educación intercultural; capital intercultural; encuesta comparativa; futuros docentes; multilingüismo; transnacionalidad

El concepto de pluriformidad cultural y su relevancia para la educación intercultural: Una perspectiva crítica desde Bourdieu - Pöllmann, Andreas (MODULEMA. Revista científica sobre Diversidad Cultural)
Basándose en el marco conceptual de Pierre Bourdieu, este artículo presenta la noción de pluriformidad cultural y su relevancia para una educación intercultural crítica, inclusiva y equitativa. Situado en el nexo de las nociones bourdianas de habitus, campo y doxa, el concepto de pluriformidad cultural se refiere a la coocurrencia de diferentes formas de capital cultural e intercultural dentro de un mismo individuo o campo. El análisis crítico y exploratorio de la pluriformidad cultural ofrece una alternativa viable a las prescripciones normativas de lo que supuestamente significa ser competente interculturalmente. El artículo sostiene que el concepto de pluriformidad cultural resulta especialmente apropiado para cuestionar críticamente los contextos institucionales monolingües (por ejemplo, en las escuelas) que no reconocen ni valoran adecuadamente la diversidad lingüística y cultural real del alumnado. Al hacerlo, ilustra que la investigación empírica de la pluriformidad cultural en los niveles de incorporación, objetivación e institucionalización requiere especial atención de la colaboración empática e inclusiva de investigadores y sujetos de investigación.

Exploring intersectional interculturality in contexts of cultural pluriformity - Pöllmann, Andreas (Intercultural Education)
Drawing on Bourdieu’s work, this article outlines the notions of cultural pluriformity and intersectional interculturality. The concept of cultural pluriformity refers to the co-occurrence of different (inter)cultural resources within the same individual or field. The notion of intersectional interculturality highlights the importance of considering not only which individually embodied (inter)cultural resources are recognised and valued in educational fields, but also whose. In doing so, it acknowledges that individuals may be more or less self-conscious, assertive, and persistent when it comes to self-attributions in terms of socially and culturally relevant categories such as class, gender, race, nationality, citizenship status, religious affiliation, age, sexual orientation, health, and ability. The respective self-attributions may be more or less consistent with pertinent external attributions – including those expressed by other individuals as well as those materialised in the context of relevant cultural and intercultural objectifications and institutionalisations. The open-ended exploration of intersectional interculturality in contexts of cultural pluriformity offers opportunities for introspection, collaboration, and empathy, with a genuine potential for reflexive and dialogical intercultural competence development. Instead of treating ‘culture’ as some sort of essentialised explanatory force, it is jointly explored as a variable phenomenon, with an analytical focus on intra-individual, inter-individual, and structural factors.

Brexit and European Corporate Bond Markets - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
We investigate the impact of Brexit on the corporate bond market by analyzing a comprehensive database covering corporate bond listings on European and UK trading venues. We find a significant shift in bond market activity, evidenced by a 49% increase in the number of bond listings in the EEA30 countries relative to the UK market after Brexit. Country-level analyses reveal a staggered effect on market activity, with predominantly international issuers adjusting their bond listings between the initially scheduled Brexit date and the final withdrawal date. At the issuer level, our findings indicate that the relative attractiveness of the EEA30 market has increased post-Brexit. Overall, these results suggest that the European capital market has successfully adapted to the loss of its largest financial center and exhibits a rising corporate bond market activity.

Artificial intelligence - prerequisites for competent use and assessment - Herzig, Bardo (TELEVIZION)

Molecular-scale synchrotron X-ray investigations of solid-liquid interfaces in lithium-ion batteries - Cao, Chuntian; Steinrück, Hans-Georg (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

The Swineherd’s Wife who Scolded the King - Foerster, Anne (Women in Early Medieval England)

Eadburh of Wessex - Foerster, Anne (Women in Early Medieval England)

Seaxburh - Foerster, Anne (Women in Early Medieval England)

Exploring Capabilities for the Smart Service Transformation in Manufacturing: Insights from Theory and Practice - Koldewey, Christian; Fichtler, Timm; Scholtysik, Michel; Biehler, Jan; Schreiner, Nick; Sommer, Franziska; Schacht, Maximilian; Kaufmann, Jonas; Rabe, Martin; Sedlmeier, Joachim; Dumitrescu, Roman
Digital Servitization is one of the significant trends affecting the manufacturing industry. Companies try to tackle challenges regarding their differentiation and profitability using digital services. One specific type of digital services are smart services, which are digital services built on data from smart products. Introducing these kinds of offerings into the portfolio of manufacturing companies is not trivial. Moreover, they require conscious action to align all relevant capabilities to realize the respective business goals. However, what capabilities are generally relevant for smart services remains opaque. We conducted a systematic literature review to identify them and extended the results through an interview study. Our analysis results in 78 capabilities clustered among 12 principles and six dimensions. These results provide significant support for the smart service transformation of manufacturing companies and for structuring the research field of smart services.
Keywords: Digital Servitization; Transformation; Capabilities; Maturity; Smart Services

Domain Knowledge Injection Guidance for Predictive Maintenance - Afroze, Lameya; Merkelbach, Silke; von Enzberg, Sebastian; Dumitrescu, Roman (ML4CPS 2023)

Business strategy taxonomy and solution patterns for the circular economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Liebestragödie. Genealogien einer französischen Gattung des 17. Jahrhunderts - Schlieper, Hendrik

Making “the Two” Into One Body: De- and Recategorization of (Un-)Circumcision, - Taschl-Erber, Andrea (Reconsidering the Letter to the Ephesians in Context)

Martha and Her Sister(s) – Female Voices in the Fourth Gospel, - Taschl-Erber, Andrea (More than Female Disciples: An Examination of Women’s Authority in Ancient Christianity (Ist-VIth centuries))

Evangelium für Frauen? Das dritte und vierte Evangelium im Vergleich - Taschl-Erber, Andrea (Theologie und Glaube)